KINERJA APARATUR PADA SUB BAGIAN UMUM DI DINAS PERTANIAN TANAMAN PANGAN PROVINSI KALIMANTAN TIMUR - Agus Ahmad (Magister Administrasi Publik FISIP Universitas Mulawarman, 2020)
This study describes the performance of the apparatus in the Sub Division General in the Department of Agriculture in East Kalimantan Province. Data were collected through library research, observation, interviews, and questionnaires. The results of the study will be analyzed from the results of the questionnaire and the analysis begins by describing the general picture agencies, the profile of respondents was then followed by a description of each variable analysis Apparatus Performance Department of Agriculture in East Kalimantan Province. The findings in this study is seen that the performance of employees at the Department of Agriculture in East Kalimantan Province, in general, the result of work that has been achieved in the quality and quantity of work achieved by one's employees in carrying out their duties are in accordance with the responsibilities given as expected by an Organization. Keywords : Performance, Apparatus